فکرِ اسلامی میں وبائی امراض سے متعلق علمی ردِ عمل - Muhammad Zia ul Haq; Muhammad Riaz Mahmood (Pakistan Journal of Islamic Research)
The present paper tries to analyze the academic response to pandemics and epidemics in the Islamic thought. Historically, Muslims have played an active role in eradicating various dangerous diseases.That is why the Islamic literature on Tafseer, Hadith, Jurisprudence, History and various sciences contains very useful information about the history, diagnosis, treatment, prevention, diet, precautionary measures and the after-effects of these diseases.The scholarly analysis and practical usefulness of this unique and rare literature is of great importance in the context of the present pandemic which has gripped the whole world. This study also gives an idea of ​​the breadth and depth of the scholarly services of Muslims in the fields of pandemics, epidemics, medicine and services to human civilization.